FEV Maintains Homing and Expansion by Activating ITGA4 Transcription in Primary and Relapsed AML - Zhang, Jubin; Qi, Lijuan; Wang, Tanzhen; An, Jingnan; Zhou, Biqi; Fang, Yanglan; Liu, Yujie; Shan, Meng; Hong, Dengli; Wu, Depei; Xu, Yang; Liu, Tianhui (Frontiers in Oncology, 2022)
Acute myeloid leukemia (AML) is an aggressive hematological malignancy that recurs in approximately 50% of cases. Elevated homing and uncontrolled expansion are characteristics of AML cells. Here, we identified that Fifth Ewing Variant (FEV) regulates the homing and expansion of AML cells. We found that FEV was re-expressed in 30% of primary AML samples and in almost all relapsed AML samples, and FEV expression levels were significantly higher in relapsed samples compared to primary samples. Interference of FEV expression in AML cell lines delayed leukemic progression and suppressed homing and proliferation. Moreover, FEV directly activated integrin subunit alpha 4 (ITGA4) transcription in a dose-dependent manner. Inhibition of integrin α4 activity with natalizumab (NZM) reduced the migration and colony-forming abilities of blasts and leukemic-initiating cells (LICs) in both primary and relapsed AML. Thus, our study suggested that FEV maintains the homing and expansion of AML cells by activating ITGA4 transcription and that targeting ITGA4 inhibits the colony-forming and migration capacities of blasts and LICs. Thus, these findings suggested that the FEV-ITGA4 axis may be a therapeutic target for both primary and relapsed AML.